Utilizing Crushed Clinker Brick Waste as Coarse Aggregate to Produce Concrete With Compressive Strengths Up to 40 Mpa by Adjusting The Gradation Curve - Yulius Rief Alkhaly; Khairullah Khairullah; zulfhazli zulfhazli; Ainun Mardiah; Deddy Ariska (Malikussaleh University, Aceh, Indonesia, 2023)
Aggregate gradation is measured by determining the percentage of various particle sizes in an aggregate sample using a standard sieve arrangement. Gradation is usually expressed as a curve showing the percentage of each particle size on a logarithmic scale. This curve can then be used to determine the optimum mix design for a given concrete grade. The purpose of this research is to determine the effect of adjusting the gradation of the coarse aggregate of crushed clinker bricks on the strength of concrete. Clinkers bricks are bricks that have been burned at temperatures that are excessively high. The coarse aggregate grading is adjusted according to aggregate grading limits based on SNI 7656-2012, which are divided into three types of grading limits, namely upper, middle, and lower limits. A total of 60 cylindrical 150mm x 300mm concrete specimens were used for the compressive strength tests. The findings showed that adjusting the lower limit gradation produced optimum compressive strengths of 29.09 MPa, 35.08 MPa, 39.96 MPa, and 38.82 MPa, respectively, for the specified target concrete strengths of 20 MPa, 25 MPa, 30 MPa, and 35 MPa, which were higher than those of the middle and upper limit gradations. The compressive strength and density of the concrete can be significantly improved by modification of the coarse aggregate grading of the clinker bricks